The role and importance of the command in educating cadets on the basis of spiritual and moral values in higher military educational institutions (Journal of Pedagogical Inventions and Practices, 2022)
This article is about the role of command in moral and moral education of cadets studying in higher military educational institutions and the role of command in raising cadets to become well-rounded, highly moral people